Case marketing in Nubri - Donohue, Cathryn (Nepalese Linguistics, 2018)
This paper introduces the case marking system in Nubri, using data from both Samagaun and Prok villages. Nubri, a Tibetic language, has ergative and dative morphological cases, but appears to have a dispreference for using morphological case where possible. This paper explores this issue, comparing the variations between the two dialects.